2015
DOI: 10.1155/2015/583549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of One-Week Tongue-Task Training on Sleep Apnea Severity: A Pilot Study

Abstract: The aim of the present study was to assess the effects of one-week tongue-task training (TTT) on sleep apnea severity in sleep apnea subjects. Ten patients with sleep apnea (seven men, mean [± SD] age 52 ± 8 years; mean apnea-hypopnea [AHI] index 20.9 ± 5.3 events/h) underwent 1 h TTT in the authors' laboratory on seven consecutive days. A complete or limited recording and tongue maximal protruding force were assessed before and after one-week TTT. One-week TTT was associated with a global AHI decrease (pre-TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
5
9
0
1
Order By: Relevance
“…This has been documented for the masseter muscle, whose mechanical performance improved following low-intensity motor task training (17). These results are consistent with the decrease in AHI observed after 1 wk of tongue task training (35).…”
Section: Clinical and Physiological Implicationssupporting
confidence: 85%
“…This has been documented for the masseter muscle, whose mechanical performance improved following low-intensity motor task training (17). These results are consistent with the decrease in AHI observed after 1 wk of tongue task training (35).…”
Section: Clinical and Physiological Implicationssupporting
confidence: 85%
“…One reported that one-week tongue task training improved disordered breathing in OSA patients (OSA severity decreased from moderate to mild in 50% of subjects, and a 48% decrease of obstructive breathing disturbance was observed during rapid eye movement stage), while maximum protruding force training remained unchanged. [27] Our research further confirmed that tongue task training is not oriented toward strength gain, but rather toward an enhancement in genioglossus cortical excitability and improvement in the coordination of the genioglossus protrusion task. There are still some issues deserves further investigation, such as who will benefit more from this approach and the design of the suitable upper airway muscle training?…”
Section: Upper Airway Muscle Trainingsupporting
confidence: 76%
“…These abnormalities may contribute to obstructive events during sleep by promoting upper airways unstability [ 16 ]. This probably explains why “functional” treatment, such as pharyngeal muscle retraining which acts via a combination of increased strength of the genioglossus, the main dilator muscle of the upper airways, and neuromodulating adaptations [ 17 ], has been shown to effectively reduce the apnoea-hypopnoea index (AHI) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%